On the Convergence Rate for the Longest at Most T-Contaminated Runs of Heads - István Fazekas; Borbála Fazekas; László Fórián (Entropy)
In this paper, we study the usual coin tossing experiment. We call a run at most T-contaminated, if it contains at most T tails. We approximate the distribution of the length of the longest at most T-contaminated runs. We offer a more precise approximation than the previous one.